2021
DOI: 10.3390/diagnostics11091532
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography-Navigation™ Electromagnetic System Compared to Conventional Computed Tomography Guidance for Percutaneous Lung Biopsy: A Single-Center Experience

Abstract: The aim of our study was to assess the efficacy of a computed tomography (CT)-Navigation™ electromagnetic system compared to conventional CT methods for percutaneous lung biopsies (PLB). In this single-center retrospective study, data of a CT-Navigation™ system guided PLB (NAV-group) and conventional CT PLB (CT-group) performed between January 2017 and February 2020 were reviewed. The primary endpoint was the diagnostic success. Secondary endpoints were technical success, total procedure duration, number of CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…However, there was no significant difference in surgical time or the number of CT scans between the 2 groups 18 . Another retrospective nonrandomized study reported that technical and diagnostic success rates, total procedure duration, total CT acquisitions and complication rates were similar between the CT-EM navigation system–guided percutaneous lung biopsies and the conventional CT guidance, but the radiation dose was significantly reduced with EM navigation 19 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, there was no significant difference in surgical time or the number of CT scans between the 2 groups 18 . Another retrospective nonrandomized study reported that technical and diagnostic success rates, total procedure duration, total CT acquisitions and complication rates were similar between the CT-EM navigation system–guided percutaneous lung biopsies and the conventional CT guidance, but the radiation dose was significantly reduced with EM navigation 19 …”
Section: Discussionmentioning
confidence: 98%
“…18 Another retrospective nonrandomized study reported that technical and diagnostic success rates, total procedure duration, total CT acquisitions and complication rates were similar between the CT-EM navigation system-guided percutaneous lung biopsies and the conventional CT guidance, but the radiation dose was significantly reduced with EM navigation. 19 To further investigate the clinical value of EM navigation systems, we performed this prospective clinical study. The results from our trial suggest that compared with conventional approaches, CT-guided percutaneous lung biopsy with EM navigation is helpful for reducing the number of needle adjustments.…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility and safety of the robotic-assisted insertion of biopsy introducer needles have been assessed with a variety of systems in a spectrum of studies, including different target locations [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. Biopsy sessions were feasible in all patients with accurate needle targeting of the lesion [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ].…”
Section: Clinical Applications and The Literature Evidencementioning
confidence: 99%
“…The feasibility and safety of the robotic-assisted insertion of biopsy introducer needles have been assessed with a variety of systems in a spectrum of studies, including different target locations [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. Biopsy sessions were feasible in all patients with accurate needle targeting of the lesion [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. The performance of a robotic system for CT-guided lung biopsy in comparison to the conventional manual technique was evaluated in a study of 100 patients, which showed that robot-assisted CT-guided lung biopsy was safe, with high diagnostic accuracy, and reduced procedure times and radiation doses in comparison to the conventional freehand technique.…”
Section: Clinical Applications and The Literature Evidencementioning
confidence: 99%